1985
DOI: 10.1007/bf00008938
|View full text |Cite
|
Sign up to set email alerts
|

Ecological survey of the aquatic oligochaetes in the Lower Pearl River (People's Republic of China)

Abstract: The species composition, distribution and abundance of the Tubificidae (8 spp.) and Naididae (at least 4 spp.) in the Guangzhou reach of the Lower Pearl River were investigated. Limnodrilus spp. (particularly L. hoffmeisteri) constitutes the greatest part in nearly all samples, which were taken in both clean and polluted parts of the reach. In the polluted sites, total oligochaete densities reach values of up to 700 000 ind. m-2. The importance and problems of using oligochaetes as indicators of organic pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, the density thresholds in this study may not be suitable for other cases since it is difficult to ensure the standards of different pollution states and because the impacts of organic pollutants on oligochaete community structure are not fully demonstrated or understood (Sang & Erséus, 1985). Although oligochaetes generally occur in polluted places they may be absent or minimal due to unfavorable oxygen regimes and sediments (Slepukhina, 1984), or the excessive presence of chemical pollutants such as PAHs, PCBs, and heavy metals (Prygiel et al, 2000).…”
Section: Applications Of Pollution Assessments and Biotic Indicesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the density thresholds in this study may not be suitable for other cases since it is difficult to ensure the standards of different pollution states and because the impacts of organic pollutants on oligochaete community structure are not fully demonstrated or understood (Sang & Erséus, 1985). Although oligochaetes generally occur in polluted places they may be absent or minimal due to unfavorable oxygen regimes and sediments (Slepukhina, 1984), or the excessive presence of chemical pollutants such as PAHs, PCBs, and heavy metals (Prygiel et al, 2000).…”
Section: Applications Of Pollution Assessments and Biotic Indicesmentioning
confidence: 97%
“…In addition, climactic or tropic conditions may also be limiting factors for the oligochaete population density in different regions. For example, oligochaete density has been reported over 1,320,000 idv./m 2 (only L. hoffmeisteri) in the Keelung River, Northern Taiwan (Hsieh et al, 1998), at 700,000 idv./m 2 in the lower Pearl River, southern China (Sang & Erséus, 1985), but lower than 10,000 idv./m 2 in the urban watercourses of Ussurisk, Eastern Russia (Timm, 1997).…”
Section: Applications Of Pollution Assessments and Biotic Indicesmentioning
confidence: 97%
“…Although the Zhujiang experiences tidal cycles similar to those of the South China Sea, into which it discharges, the area is, except for its lowest portion, freshwater (Table 1). Guangzhou, the largest city in southern China, and other towns within the area use the water without desalination, and for most of the year the salinity is less than 0,5%, (Qi & Ers6us, 1985). During 1988 and 1989 several specimens of a previously unknown heteronemertean were found by Q.S.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the classification of 'moderately polluted areas' with individuals >1000 species / m 2 in Kuwait Bay sites showed evidences to studies [6,22].…”
Section: Resultsmentioning
confidence: 70%
“…Several investigators observed metal concentrations in aquatic macro benthic organisms to be a better indicator than ambient (water) metal concentrations [2,7,11,12]. Studies revealed oligochaetes as an indicator to organic and industrial pollution [6,22]. They suggested that if benthos occurs in a density of 100-999 individuals/m 2 , the water is unpolluted; 1000-5000 individuals/m 2 , moderately polluted; and more than 5000 individuals/m 2 shows heavy pollution.…”
Section: Introductionmentioning
confidence: 99%